Preparation and characterization of a pH-responsive membrane carrier for meso-tetraphenylsulfonato porphyrin. Issue 3 (5th January 2017) - Wang, Mingxia; Yan, Feng; Zhao, Lizhi; Zhang, Yuzhong; Sorci, Mirco
Abstract : The pH-responsive PSF- g -P4VP-blended PSF membrane smartly rejects meso -tetraphenylsulfonato porphyrin (TPPS) and induces TPPS to form J-type aggregates. Abstract : A pH-responsive polysulfone- graft -poly(4-vinylpyridine) (PSF- g -P4VP)-blended PSF membrane was prepared for "smart" rejection of meso -tetraphenylsulfonato porphyrin (TPPS) in the feed. The pH-responsive characteristics of the PSF- g -P4VP-blended PSF membranes were determined. The hydraulic permeation results demonstrated that the pH-responsive characteristics behaved as expected, as these were reversible and durable, and occurred with the pH value switching between 3.0 and 8.0. Water flux drastically increased from 70 to 1113 L m −2 h −1 at pH 8.0 as the content of PSF- g -P4VP polymer in the blended membrane increased from 10% to 30%. The static adsorption of TPPS on the pH-responsive blended membrane showed that the adsorption capacity dramatically depended on pH. The pH-sensitive membrane not only plays the role of a smart membrane for rejecting the aggregates of TPPS, but also induces TPPS to assemble on the membrane surface. The flux decreases, whereas the retention of TPPS increases with the decreasing pH. The value of flux was not more than 30 L m −2 h −1 at a pH below 3.0, which provides plenty of time for the self-assembly process of TPPS on the membrane surface. J-aggregates of TPPS were observed on the blended membrane surface below pH 2.5, owing to the inductive effect of cationic P4VP units, whereas J-type aggregates could be only found at pH 1.0 in an aqueous solution.